Tricomaker: o híbrido das produções em malharias retilíneas com as impressoras 3D - Pieroni, Willian [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The present Project of Conclusion of the Course of Design, with a theoretical-practical character and multidisciplinary, proposes one of the objectives the analysis of the interactions between 3D printers in the processes of production in knitting. It intends to point out possibilities of adding knits and printed accessories. Contemplate the dialogue of contemporary language, Culture Maker, with the traditional processes of textile industries. The geographic scenario is the national knit pole, located in Monte Sião, Minas Gerais. The idea of user customization and participation in the manufacturing process are projectual steps. The final product presents results of experiments with knitting and three-dimensional prints, as well as the idealization of a space of continuity of results.

O presente Projeto de Conclusão do Curso de Design, com caráter teórico-prático e multidisciplinar, propõe como um dos objetivos a análise das interações entre impressoras 3D nos processos de produção em tricô. Pretende apontar possibilidades de agregar malhas e acessórios impressos. Contempla o diálogo da linguagem contemporânea, Cultura Maker, com os tradicionais processos de indústrias têxteis. O cenário geográfico é o polo de malhas nacional, localizado em Monte Sião, Minas Gerais. A ideia de personalização e participação do usuário no processo de fabricação são etapas projetuais. O produto final coloca em cena resultados de experimentações com tricô e impressos tridimensionais, além da idealização de um espaço de continuidade dos resultados.
Tricomaker: the hybrid of straight knitting productions with 3D printers
Keywords: Maker; Tricô; Impressão 3D